Middle Ear Actinomycosis - Coutinho, Gil; Spratley, Jorge; Saldanha, Inês; Castro, Cristina; Pinheiro, Jorge; Santos, Margarida (Journal of Pediatric Infectious Diseases, 2020)
Middle ear actinomycosis is an atypical and exceedingly rare anaerobic infection. The authors report a case of a 7-year-old girl with persistent right side otalgia, conductive hearing loss, and headache. Otoscopic findings included a thickened, intact, and bulging tympanic membrane. Computed tomography imaging revealed soft tissue density filling the middle ear with areas of bone erosion. Typical sulfur granules were found on surgical exploration. Actinomycosis was diagnosed by histopathological examination. Penicillin was prescribed for 5 weeks followed by oral amoxicillin for 6 months. Recovery was uneventful and with a 2-year follow-up, no recurrence or complications were observed.
Keywords: otitis media; actinomycosis; sulfur granules